Applied Olfactory Cognition - Ilona Croy (Frontiers Research Topics, 2014)
Foreword by Richard J. Stevenson, Macquarie University (Australia): It was long thought that the human nose might be able to discriminate somewhere in the order of 10,000 different odourants. The recent finding that the human nose can discriminate something like a trillion different smells serves as yet another reminder that we have again underestimated the capacity of our sense of smell (Bushdid, Magnasco, Vosshall & Keller, 2014). This volume serves as a further corrective for anyone who should hold the view that olfaction is unimportant in human affairs. The papers presented in this ebook, carefully collated and overseen by Aldo Zucco, Benoist Schaal, Mats Olsson and Ilona Croy, showcase a large number of quite different reasons for studying the applied side of olfaction, and indeed human olfaction in general. The 23 contributions presented here cover a broad range of topics, which illustrate contemporary interests in our field. Although with a strong applied focus, a noteworthy feature of this ebook is the richness of the theoretical perspectives that are developed. These range from considerations of olfactory perception, memory, expertise, and priming right the way through to receptor genetics. These contributions, from many leading experts in the field, will surely shape much of the applied work linking olfaction to disease, which is a further focus of this ebook. In respect to health and disease, the chapters on aging, pregnancy, depression, alcohol dependency and environmental odours, present overviews and rich new data on many contemporary problems, to which the study of olfaction is now contributing. A particularly notable aspect of olfactory experience is the affective impact that odours can have on people and their lives. The ebook covers some particularly intriguing aspects of work in this area, with empirical studies investigating dissociations between wanting and liking, stress reduction in the elderly, mother-infant bonding, and the emotions that different odourants can evoke. This affective line of work is nicely complemented by empirical studies on expertise, the effect of odours on visual attention, and the relationship between particular personality traits and interest in olfaction. The gradual appropriation of methods from cognitive neuroscience into olfaction is also nicely represented in this ebook, with at least three of the chapters reporting data using neuroimaging, including a particular intriguing study looking at recognition of odours in mixtures. Finally, the close links between olfactory perception and sensory evaluation are also reflected in a chapter on wine. I hope that readers of this e-book will be struck, as I have been in reading its various chapters, how much olfaction affects our lives, and how the study of this sense can enrich it.